2016
DOI: 10.1016/j.apergo.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

What makes icons appealing? The role of processing fluency in predicting icon appeal in different task contexts

Abstract: Although icons appear on almost all interfaces, there is a paucity of research examining the determinants of icon appeal. The experiments reported here examined the icon characteristics determining appeal and the extent to which processing fluency -the subjective ease with which individuals process information -was used as a heuristic to guide appeal evaluations. Participants searched for, and identified, icons in displays. The initial appeal of icons was held constant while ease of processing was manipulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 90 publications
0
15
1
Order By: Relevance
“…Most previous studies on the effect of familiarity have employed stimuli with preexisting differences in familiarity (Blalock, 2015; Cowan et al., 2015; McDougall et al., 2016; Siedenburg & McAdams, 2017). For example, McDougall et al. (2016) used preexisting icons as stimuli, dividing them into familiar and unfamiliar groups based on participants’ ratings and found that this varied considerably between individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies on the effect of familiarity have employed stimuli with preexisting differences in familiarity (Blalock, 2015; Cowan et al., 2015; McDougall et al., 2016; Siedenburg & McAdams, 2017). For example, McDougall et al. (2016) used preexisting icons as stimuli, dividing them into familiar and unfamiliar groups based on participants’ ratings and found that this varied considerably between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…(2007) defined icon familiarity as the frequency of use, which relates directly to experience with an icon, and they believed that this form of familiarity could be trained by presenting participants with icons over a number of blocks of trials. Subsequent experimental findings of icon familiarity showed that the importance of icon characteristics changed with user experience (McDougall et al., 2016).…”
mentioning
confidence: 99%
“…Generally, findings from the current study showed that the image presented in the icon is the key point on which the perceived quality of the icon depends [ 44 , 45 ], and the preference of users for the icon may rely on this. In this case, designers may consider the cognitive features of an icon such as its familiarity, its concreteness, the complexity of the design intricated on it, its meaningfulness, and its semantic distance or its closeness to its intended meaning [ 20 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adjective pairs related to visual qualities of graphical user interface icons were added as suggested per the previous literature. These adjectives include concrete and abstract (Arend et al 1987;Blankenberger and Hahn 1991;Dewar 1999;Hou and Ho 2013;Isherwood et al 2007;McDougall and Reppa 2008;McDougall et al 1999McDougall et al , 2000Moyes and Jordan 1993;Rogers and Oborne 1987), simple and complex (Choi and Lee 2012;Goonetilleke et al 2001;McDougall and Reppa 2008;McDougall and Reppa 2013;McDougall et al 2016) as well as unique and ordinary (Creusen and Schoormans 2005;Creusen et al 2010;Dewar 1999;Goonetilleke et al 2001;Huang et al 2002;Salman et al 2010). Furthermore, adjective pairs that measure the aesthetics of graphical user interface elements were added.…”
Section: Measure Developmentmentioning
confidence: 99%